2014
DOI: 10.1002/2013jd020594
|View full text |Cite
|
Sign up to set email alerts
|

The low-level jet dust emission mechanism in the central Sahara: Observations from Bordj-Badji Mokhtar during the June 2011 Fennec Intensive Observation Period

Abstract: This paper presents the first detailed analysis of low-level jets (LLJs) in the central Sahara from ground-based observations at Bordj-Badji Mokhtar, Algeria, and addresses their operation as a dust emission mechanism. On LLJ mornings, composite wind speeds in the core (300 m aboveground level) reach 13.5 m s À1 at 0400. Surface temperatures increase from 0545 (30 min after sunrise), and jet decay begins around 0600. Ten meter winds lag those in the core by 5 h; peak 10 m wind speed, 7.5 m s À1 , occurs at 090… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 72 publications
(130 reference statements)
1
73
0
Order By: Relevance
“…Allen and Washington [] show that the presence of a LLJ is not a guarantee of dust emission since momentum does not always mix down to the surface. Indeed, in dusty regions it is possible that daytime turbulent mixing in the boundary layer actually decreases, because the dust reduces the sunlight reaching the surface [ Miller et al ., ; Pérez et al ., ].…”
Section: Dust Detection Methodology For June 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Allen and Washington [] show that the presence of a LLJ is not a guarantee of dust emission since momentum does not always mix down to the surface. Indeed, in dusty regions it is possible that daytime turbulent mixing in the boundary layer actually decreases, because the dust reduces the sunlight reaching the surface [ Miller et al ., ; Pérez et al ., ].…”
Section: Dust Detection Methodology For June 2012mentioning
confidence: 99%
“…As part of Fennec, eight automatic weather stations were deployed in the central Sahara [ Hobby et al ., ] and two supersites were established, in Bordj‐Badji Mokhtar, Algeria [ Marsham et al ., ], and Zouerat, Mauritania [ Todd et al ., ]. Observations from these supersites have provided new insights into Saharan dust, including among others the links between dust, cloud, and the surface energy balance [ Marsham et al ., ]; the relative importance of dust production mechanisms [ Allen et al ., ; Marsham et al ., ]; the operation of the low‐level jet dust emission mechanism [ Allen and Washington , ]; and the role of the Atlantic Inflow on the diurnal cycle of the boundary layer [ Todd et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Allen and Washington, 2014;Heinold et al, 2015;Knippertz, 2008;Schepanski et al, 2009) have indicated that the breakdown of the NLLJ over Africa can induce the downward mixing of momentum during the evolution of the boundary layer in midmorning and cause enhancement of near-surface wind speed. Here, we firstly compared the midmorning surface wind speed distribution coincident with the appearance of NLLJ with that when no NLLJ was detected.…”
Section: Nllj Effects On Dust Emissionmentioning
confidence: 99%
“…The strong surface wind will blow dust particles up from the desert surface, and the same turbulent mixing will also loft these dust particles to the upper level of the boundary layer, promoting horizontal transport. Therefore, the NLLJ may play an important role in the both dust emission and transport (Allen and Washington, 2014;Heinold et al, 2015;Knippertz, 2008;Tegen et al, 2013;Todd et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation